Metal‐Free Arylsulfonyl Radical Triggered Cascade Cyclization of Phenyl‐Linked 1, 6‐Enynes: Synthesis of 2, 3‐Dihydro‐1H‐indenes and 10a, 11‐Dihydro‐10H‐benzo[b]fluorines. Issue 23 (11th September 2022) - Hu, Lin‐Ping; Zhang, De‐Run; Huang, Xiao‐Hong; Liu, Feng‐Lin; Li, Xia; Teng, Ming‐Yu; Huang, Guo‐Li
Comprehensive Summary: Aryl sulfonyl radical triggered cascade cyclization of phenyl‐linked 1, 6‐enynes for the synthesis of biologically important indenes containing alkenyl C—X bonds and 10 a, 11‐dihydro‐10 H ‐benzo[ b ]fluorines is presented. In these radical cascade processes, three new chemical bonds, including C—S, C—C, and C—X bonds, and three C—C bonds are formed in one step. The method is attractive and valuable due to its metal‐free, mild reaction conditions, broad substrate scope and good functional group tolerance. Abstract : Aryl sulfonyl radical triggered cascade cyclization of phenyl‐linked 1, 6‐enynes with aryl sulfonyl hydrazides to provide indenes containing alkenyl C—X bonds and 10 a, 11‐dihydro‐10 H ‐benzo[ b ]fluorines under metal‐free conditions is established. This reaction proceeded smoothly and gave the corresponding products by using I2 /k2 S2 O8 and NIS/TBHP instead of expensive and toxic catalysts with the formation of C—S, C—C, and C—X bonds, and three C—C bonds in one step. This method also allowed easy access to significant functional indenes and benzo[ b ]fluorines for potential applications in medicinal and organic chemistry.